Transformasi Nilai Lokal dalam Pengelolaan Lahan Gambut Berkelanjutan : Studi Kasus Desa Dayun, Kabupaten Siak, Riau - Bram William Amadeus; Deswita Maharani Lumban Toruan; Filumena Hasugian; Flora Tresia Br. Purba; Muhammad Fathir; Nabiilah Nurza Herlambang; Wira Michael Artiofi Simanjuntak; Nurahim Rasudin (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to analyze the role of local values in the sustainable management of peatlands in Dayun Village, Siak Regency, Riau Province. The research applies a descriptive qualitative method using a normative-empirical approach. Findings indicate that although formal customary law structures are no longer present, local communities continue to apply traditional values in land management. Activities include sustainable watermelon farming, batik training using watermelon leaves, and processing agricultural products into local goods such as juices and watermelon-based snacks. Furthermore, educational tourism initiatives emphasize Malay cultural preservation, environmental awareness, and social revitalization. Community activities such as group exercises, outbound games, forest fire prevention education, and crafts training are led by the local tourism awareness group (Pokdarwis). These reflect a transformation of local values into tangible actions supporting ecological sustainability and community economic growth. The study also highlights the importance of local leadership and external collaboration in implementing these grassroots initiatives successfully.